Tratamento não-farmacológico na disfunção temporomandibular crônica: estudo preliminar, randomizado, controlado e duplo-cego - Silva, Tatyanne dos Santos Falcão (2018)
Temporomandibular Dysfunction (TMD) is a disease characterized by a set of signs and symptoms, in which the pain is a very present and striking symptom, with a tendency to chronicity. The chronic pain is a difficult treatment condition, caused by mechanisms of maladaptive neuroplasticity. In face of this, Transcranial direct current stimulation (tDCS) appears as a possible strategy for the treatment of chronic pain however, it needs further investigation of its therapeutic effect in TMD. The present study had as objective evaluate and to compare the efficacy of anodic tDCS, applied in two cortical regions separately (primary motor and dorsolateral prefrontal), in the pain symptomatology and, as well as, anxiety levels in individuals with chronic myofascial TMD. Therefore, a randomized, double-blind, controlled, cross-over, preliminary study was conducted. Individuals diagnosed with TMD chronic muscular were included by RDC/TMD. They received three different types of intervention whose order was randomized: anodic in the left primary motor cortex (M1), in the left dorsolateral prefrontal cortex (DLPFC) and sham stimulation. The intervention occurred daily (excluding the weekend) for a period of twenty minutes, during a week, totaling 05 sessions. Participants were assessed in relation to the intensity of pain and anxiety before and after treatment, through the following instruments: Visual Analog Scale (VAS) and State-trait anxiety Inventory (STAI), respectively. There were significant improvements in clinical pain in all stimulation protocols, with a relief of approximately 40% through the Visual Analogue Scale (p=0.001). There was no significant difference in the effect of tDCS between the different types of stimulation (p = 0.14). There was a positive impact in anxiety symptoms tracked by IDATE, revealing a significant decrease in state anxiety levels (p=0.035) and trait (p=0.009) after treatment. However, there was no difference between the types of stimulation in both the anxiety state (p=0.43) and trait (p=0.69). Participants reported a moderate change, but significant in their health status, development of their daily activities, emotions and quality of life. It was concluded that the use of tDCS improved the health status of patients with chronic myofascial TMD, promoting relief of pain, decreased level of anxiety, and quality of life.